Surface enhanced Raman spectroscopic (SERS) behavior of substituted propenoic acids used in heterogeneous catalytic asymmetric hydrogenation. (23rd June 2015) - Firkala, Tamás; Tálas, Emília; Kristyán, Sándor; Szöllősi, György; Drotár, Eszter; Mink, János; Mihály, Judith
Abstract : The strength and geometry of adsorption of substituted propenoic acids on silver surface were studied by means of surface enhanced Raman spectroscopy (SERS) using silver sol. Based on their SERS behavior, two classes of phenylpropenoic acids studied were distinguished. The first class of propenoic acids (atropic acid, ( E )‐2, 3‐diphenylpropenoic acid, ( E )‐2‐(2‐methoxyphenyl)‐3‐phenylpropenoic acid, ( E )‐2, 3‐di‐(4‐methoxyphenyl)phenylpropenoic acid and ( E )‐2‐(2‐methoxyphenyl)‐3‐(4‐fluorophenyl)propenoic acid) has shown strong charge transfer (CT) effect. We suggest bidentate carboxyl bonded species based on the SERS enhanced bands of νCOO − around 1394 cm −1 and νC―C of the ―C―COO − moiety at 951 cm −1 . In these series the plane of the α‐phenyl group (γCH out‐of‐plane vibrations at 850–700 cm −1 ) is almost parallel to the silver surface, while the β‐phenyl group is in tilted position depending on the type and the position of substituent(s) showing strong SERS enhanced bands of νCC + βCH (in‐plane mode) at 1075 cm −1, νCC (ring breathing mode, in‐plane) at 1000 cm −1 and γCCC (out‐of‐plane mode) around 401 cm −1 . The other class of propenoic acids (cinnamic acid, ( E )‐2‐phenyl‐3‐(4‐methoxyphenyl)propenoic acid) has shown weak electromagnetic (EM) enhancement (CC bands is enhanced in cinnamic acid). In this case no significant carboxyl enhancement was observed, so we suggest that adsorbed species lie parallel to the surface. The two types of adsorption can be related to the dissociation ability of the carboxylic group. In the first case the carboxylic H dissociates, while in the second case it does not, as indicated also by the characteristic νCO band at 1686 cm −1 in the FT‐Raman spectra of methanolic solutions. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Based on their SERS behavior, two classes of the studied phenylpropenoic acids were distinguished: series (I) with strong charge transfer (CT) effect and bidentate carboxyl‐bonded species based on the SERS enhanced bands of νCOO − around 1394 cm −1 and νC―C of the ―C―COO − moiety at 951 cm −1 ; series (II) with only weak electromagnetic enhancement (EM) without significant carboxyl enhancement. The two types of adsorption can be related to the dissociation ability of the carboxylic group.